Self-Reliant Learning Strategy in Vocational and Technical Education: Insights from Group Collaboration - Yussop, Muhammad Abdul Hanif; Shahrill, Masitah; Abdul Latif, Siti Norhedayah (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2021)
In this study, a self-reliant learning strategy was used in the teaching and learning of a Mathematics module at a local technical institution to investigate its effectiveness in improving the students' performance in descriptive statistics. This study also examined how group work activity, when integrated with the self-reliant strategy, can contribute to students' development in directing their learning. Forty-two students were observed on how a self-reliant learning strategy affects their performance. It is found that the self-reliant learning strategy had a positive impact on the students' performance in their learning of descriptive statistics and that group work activity improved students' learning skills, especially on planning, monitoring, and evaluating their course of learning on their own. The findings of this study hoped to provide pedagogical alternatives and persuade teachers to consider the self-reliant learning strategy that promotes flexibility in the course of the students' learning.